Investigation of Vitamin K Quinone Metabolism by Human Gut Bacteria. (29th May 2020) - Ellis, Jessie; Fu, Xueyan; Karl, J Philip; Radcliffe, Patrick; Soares, Jason; Doherty, Laurel; Hernandez, Christopher; Mason, Joel; Oliverio, Angela; Booth, Sarah
Abstract: Objectives: Vitamin K (VK) is a family of structurally-related quinones, phylloquinone (PK) and menaquinones (MKn, n = prenyl units in side chain), that share a common napthoquinone ring (menadione, MD). VK quinones function as an essential dietary nutrient for humans. MD is considered a pro-vitamin form of VK. Plants and bacteria that produce VK quinones (PK and MKn, respectively) use them as an electron carrier in energy production. Little is known about the interaction of dietary VK quinones with gut bacteria, which may be bi-directional. The objective of this study was to investigate the influence of VK quinones and MD on human gut bacteria composition and MKn production. Methods: Stool from 5 healthy male donors was pooled and inoculated in bioreactors under conditions mimicking the colon (anaerobic, pH 6.8, 37°C) for 48 h. Bioreactors were treated with deuterium ( 2 H)-labeled quinones ( 2 H-PK, 2 H-MK4, 2 H-MK9 or 2 H-MD); no quinones (cell controls); or 2 H-quinone treatment with no stool (cell-free controls). Culture aliquots were collected at 0, 5, 10, 24, and 48 h, and separated into pellet and supernatant fractions. Experiments were conducted in triplicate. All fractions were analyzed for VK quinone content using LC-MS. DNA from 0 and 24 h pellet fractions was extracted and amplified for paired-end 16S sequencing on an Illumina MiSeq 2500. Differences in bacterial composition were assessed using PERMANOVA. Results: Supplemented 2 H-quinones accumulated in the pellet fraction over time. This was not observed in cell-free controls and was thus not a function of culture media solubility. Endogenous (unlabeled) production of MKn was unaffected by supplementation of 2 H-quinones. Generated 2 H-MKn ( 2 H-MK4, 2 H-MK9, 2 H-MK10, and 2 H-MK11) were only detected in 2 H-MD supplemented vessels. Community-wide bacterial composition significantly differed between 0 h and 24 h (r 2 = 0.85, P = 0.001), but not by quinone treatment. Conclusions: PK and MKn, dietary viamin K quinones, were not transformed by gut microbes to MKn in vitro, whereas the pro-vitamin quinone MD was transformed to MKn of multiple side chain lengths. Although no quinone induced community-wide changes in bacteria composition, additional analyses are needed to assess species-specific growth promotion. Funding Sources: USDA ARS and DOD Health Program.